ANALISIS DAN PERANCANGAN ONLINE ANALYTICAL PROCESSING SEBAGAI BUSINESS INTELLIGENCE PADA SEKOLAH MUSIK CANTATA - Yunus Fadhillah (Jurnal Informatika dan Bisnis, 2017)
Cantata Music School is the object of the research conducted by the author. In the process of collecting data and information through direct observation and interviews with the relevant part is Managing Director and IT support Cantata Music School. The use of a database using the original structure of the historical data Cantata academic information systems. The results of the research conducted was a "Pupil OLAP Cantata" which consists of the manufacturing process the data warehouse to the analysis process that produces the report as decision support Cantata School owners to be more precise, accurate, and reliable.The conclusion of the analysis and design of OLAP are student data can be integrated in a storage area that allows users to access, process data quickly and accurately, and to help school owners to make decisions that are reliable and trustworthy. Keywords: OLAP, Business Intelligence, Data Warehouse, Pentaho Data Integration, Java, Multidimensional